2020
DOI: 10.2215/cjn.08430520
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Strategies and Filter Life in COVID-19 Patients Receiving Continuous Renal Replacement Therapy

Abstract: Because of the unprecedented increase in critically ill patients with coronavirus disease 2019 (COVID-19), capacity to provide continuous RRT (CRRT) for AKI may quickly be overwhelmed (1). Exacerbating this resource crunch is the hypercoagulability observed in COVID-19 (2,3). Frequent CRRT circuit clotting leads to blood loss and wastage of already overextended resources, and need for troubleshooting increases health care provider exposure to infected patients. At our quaternary care academic institution, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 5 publications
7
37
0
4
Order By: Relevance
“…The article describes the filter life of 52 critically ill patients with COVID-19 who required prolonged intermittent RRT via sustained, low-efficiency dialysis compared with a control group of patients without COVID-19 in the same center. Similarly to the study by Shankaranarayanan et al (9), they found that treatment with systemic heparin prolonged the duration of dialysis to 12.3 (interquartile range [IQR], 7.2-24.5) hours compared with 4.5 (IQR, 2.5-9.3) hours with citrate or 4.1 (IQR, 2.5-11.3) hours with no anticoagulation. Compared with patients receiving similar CRRT treatments in the pre-COVID-19 era, filter lives were reduced by 50%, and there was a nine-fold increase in the use of heparin, with a corresponding two-fold increase in bleeding complications.…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…The article describes the filter life of 52 critically ill patients with COVID-19 who required prolonged intermittent RRT via sustained, low-efficiency dialysis compared with a control group of patients without COVID-19 in the same center. Similarly to the study by Shankaranarayanan et al (9), they found that treatment with systemic heparin prolonged the duration of dialysis to 12.3 (interquartile range [IQR], 7.2-24.5) hours compared with 4.5 (IQR, 2.5-9.3) hours with citrate or 4.1 (IQR, 2.5-11.3) hours with no anticoagulation. Compared with patients receiving similar CRRT treatments in the pre-COVID-19 era, filter lives were reduced by 50%, and there was a nine-fold increase in the use of heparin, with a corresponding two-fold increase in bleeding complications.…”
mentioning
confidence: 54%
“…The presumption from these data is that systemic hypercoagulability of COVID-19 leads to decreased filter life from clotting, which is supported by high rates of venous thromboembolism in this population, and the use of systemic heparin results in a longer filter life span (9). Hypercoagulability correlates with inflammation during severe COVID-19 and it has been speculated that systemic heparin might decrease thrombosis of large and small arteries, leading to improved clinical outcomes in some patients who are severely ill (11).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Since our patient's discharge from hospital, a single-center study has suggested argatroban to be effective when utilized as an escalation therapy in patients with COVID-19 who have already developed thromboembolism and who require continuous RRT. 21 Additionally, argatroban use has been described in a small group of patients more profoundly critically ill with SARS-CoV-2 infection, most of whom required extracorporeal membrane oxygenation (ECMO). 22 Aside from RRT and ECMO, an extracorporeal approach to removing circulating SARS-CoV-2 from the bloodstream is also being explored 23 ; effective anticoagulation strategies will be essential if such extracorporeal therapies are to be successful.…”
Section: Figmentioning
confidence: 99%